Penjadwalan staf PT. Adi Sarana Logistik Divisi Outbound Unit Picker dan Dispatcher berdasarkan Minimisasi Jam lembur - Silalahi, Agustinus; Heryanto, Timotius; Hidayat, Trifenaus Prabu; Hutahaean, Hotma Antoni; Indriati, Kumala (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
PT. Adi Sarana Logistik (PT ASL) is a company engaged in the warehouse and logistics sector, which delivers many packages daily. Previously, manual scheduling took a long time, and there were violations of working hours regulations. The research was conducted at the outbound division, in picker and dispatcher units for leaders and operational staff, where the number of operational staff varies each month, so there are four schedules were produced where this study aims to minimize overtime hours for each level of staffs and units by Goal Programming and Binary Integer Programming which are completed with LINGO 18.0. The results of this study have been implemented in the company, where the schedule only takes a few seconds, while previously, it took 1-2 days. The scheduling carried out in this study is in October 2022, where all employees for leaders and staff in each unit have 22 working days, nine days off, 1 hour of overtime, and follow the rules.